UPAYA PEMERINTAH KABUPATEN KEPULAUAN MERANTI DALAM PENYEDIAAN AIR BERSIH DI KECAMATAN TEBING TINGGI TAHUN 2012-2014 - Susanti, Dwi; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
THIS  research is motivated by the defunct local company’s drinking water, so the need for water is a mobdatory requirement for the community. Water inftrastructure is one that is important to remember that water is a basic requirement is always consumed. The purpose of this study to influence the district govermment meranti islands and the inhibiting factors in the provision of clean water. The method used is a qualitatif research method with a descriptive type of reasearch that can be defined that can be interprated as a problems-solving process to describe the state of the subject and object of reseacrh at the presesnt time based on the facts that appear. Basa on the research that govermment efforts are still not up to the water supply in the districh high clifss theree are several factors that influence the govermment, namely the geographical conditions and economic factors Keywords : disctrict government, in provition of clean water.